Quantifying gait deviations in individuals with rheumatoid arthritis using the Gait Deviation Index. (March 2014) - Esbjörnsson, A-C; Rozumalski, A; Iversen, MD; Schwartz, MH; Wretenberg, P; Broström, EW
<x xml:space="preserve">Abstract</x> Objectives: In this study we evaluated the usability of the Gait Deviation Index (GDI), an index that summarizes the amount of deviation in movement from a standard norm, in adults with rheumatoid arthritis (RA). The aims of the study were to evaluate the ability of the GDI to identify gait deviations, assess inter-trial repeatability, and examine the relationship between the GDI and walking speed, physical disability, and pain. Method: Sixty-three adults with RA and 59 adults with typical gait patterns were included in this retrospective case–control study. Following a three-dimensional gait analysis (3DGA), representative gait cycles were selected and GDI scores calculated. To evaluate the effect of walking speed, GDI scores were calculated using both a free-speed and a speed-matched reference set. Physical disability was assessed using the Health Assessment Questionnaire (HAQ) and subjects rated their pain during walking. Results: Adults with RA had significantly increased gait deviations compared to healthy individuals, as shown by lower GDI scores [87.9 (SD = 8.7) vs. 99.4 (SD = 8.3), p < 0.001]. This difference was also seen when adjusting for walking speed [91.7 (SD = 9.0) vs. 99.9 (SD = 8.6), p < 0.001]. It was estimated that a change of ≥ 5 GDI units was required to account for natural variation in gait. There was no evident relationship between GDI and low/high RA-related physical disability and pain. Conclusions: The GDI seems to useful for identifying and summarizing gait deviations in individuals with RA. Thus, we consider that the GDI provides an overall measure of gait deviation that may reflect lower extremity pathology and may help clinicians to understand the impact of RA on gait dynamics.